Education and MST: analysis on the scholar situation of children in Acampamento Marielle Vive! during the Covid-19 pandemic - Fabiana de Cássia Rodrigues; Julia Pacheco e Zan (Universidade Federal do Norte do Tocantins, 2024)
This text aims at discussing the way in which the school care for the kids of Acampamento Marielle Vive! camp happened, between March 2020 and July 2021, showing the difficulties aggravated by the Pandemic, between them: structural obstacles for carrying out school activities, caused by the lack of care by the State; the absence of corrections and monitoring by teachers; and the social-economic situation of the families, impaired by the unemployment's increase in the country. The investigation's methodology followed a qualitative approach based on: bibliographical sources, documents on the education policy from the city - decrees and other regulations on education in Valinhos during the referred period -, besides the general regulations of the education policy during the Pandemic, and interviews - carried out with the officials of the education sector at the camp, children's mothers, and people who act in the city's schools. It was possible to conclude that the necessity of self-organization occurred in parallel to the weaknesses in the school care of the municipality. In the face of all the challenges, the alternatives found by means of the mobilization of the education sector at the camp showed themselves to be effective at the care of the landless children, highlighting that the fact that they belong to a political organization as MST was decisive in the reaction during the Pandemic.